Fatigue Assessment of Ti–6Al–4V Circular Notched Specimens Produced by Selective Laser Melting - Seyed-Mohammad-Javad Razavi (Metals, 2017)
Additive manufacturing (AM) offers the potential to economically produce customized components with complex geometries in a shorter design-to-manufacture cycle. However, the basic understanding of the fatigue behavior of these materials must be substantially improved at all scale levels before the unique features of this rapidly developing technology can be used in critical load bearing applications. This work aims to assess the fatigue strength of Ti–6Al–4V smooth and circular notched samples produced by selective laser melting (SLM). Scanning Electron Microscopy (SEM) was used to investigate the fracture surface of the broken samples in order to identify crack initiation points and fracture mechanisms. Despite the observed fatigue strength reduction induced by circular notched specimens compared to smooth specimens, notched samples showed a very low notch sensitivity attributed both to hexagonal crystal lattice characteristics of tempered alpha prime grains and to surface defects induced by the SLM process itself.